Curriculum Needs of Higher Education Students Regarding Death Education in Mainland China: A Scoping Review - Duan Shengyang, Duan; Lee Jun Choi, Lee (Pakistan Journal of Life and Social Sciences, 2024)
The objective of this scoping review was to investigate the distinct requirements of higher education students in mainland China regarding death education courses. This scoping study has identified and documented the existing research information regarding the necessity of death education courses, as seen by higher education students in mainland China. The purpose was to identify any gaps in evidence and literature for future research. A thorough literature search was undertaken in June 2024, encompassing both Chinese and English languages. Five library databases were utilised, covering the period from 2005 to 2024. Following a rigorous two-step evaluation process conducted by two reviewers, following pre-established criteria for inclusion, a total of 23 publications were selected. These articles consisted of 20 Chinese studies and 3 English studies. The data from each study were extracted, documented, and analysed using thematic analysis of the content of the included publications and quantitative analysis of the scoping review. These publications disclose the requirements of mainland China higher education students about course instructors, as well as their requirements for course objectives, content, teaching methods, teaching formats, and teaching assessment systems. The requirements of students in various fields and grade levels varies, as do the needs of students with varying expectations of death education and diverse circumstances surrounding the death day. Hence, educators must to thoroughly examine the requirements of pupils and develop focused and effective curricula. Future research should focus on refining the specific requirements of students at different grade levels and academic disciplines. Additionally, it should investigate adaptable and varied teaching and assessment approaches to boost the effectiveness of the structured death education curriculum system.